2016
DOI: 10.1111/cas.13094
|View full text |Cite
|
Sign up to set email alerts
|

Reduced phosphorylation of ribosomal protein S6 is associated with sensitivity to MEK inhibition in gastric cancer cells

Abstract: Gastric cancer (GC) is characterized by amplifications of receptor tyrosine kinases (RTK) and KRAS, therefore, targeting of the RTK/KRAS downstream pathways could help to broaden the applicability of molecular targeted therapy for GC. We assembled a panel of 48 GC cell lines and screened predictors of responsiveness to inhibition of the RAF/MEK/ERK pathway, one of the RTK/KRAS downstream pathways. We found that GC cells with MET amplification or KRAS mutation, but not amplification, tended to be sensitive to M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
(71 reference statements)
0
18
0
Order By: Relevance
“…For example, a recent study revealed that GLTSCR2 regulates the MDM2-TP53 pathway through RPL11, playing a key role in GC progression [ 42 ]. A previous study has observed that reducing the phosphorylation of RPS6 could have an influence on the sensitivity to MEK inhibition in gastric cancer cells [ 43 ]. Another important pathway in GC is glycolysis/gluconeogenesis pathway.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study revealed that GLTSCR2 regulates the MDM2-TP53 pathway through RPL11, playing a key role in GC progression [ 42 ]. A previous study has observed that reducing the phosphorylation of RPS6 could have an influence on the sensitivity to MEK inhibition in gastric cancer cells [ 43 ]. Another important pathway in GC is glycolysis/gluconeogenesis pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Examining the cell yield of these inhibitors compared to the respective uninhibited control conditions in their respective batches, we found that the cell yield of the Cluster D inhibitors was on average 60% lower than the TGF-β-only controls (Supplementary Table 4). Based on these findings and a prior report suggesting that decreased phosphorylation of ribosomal protein S6 may be associated with sensitivity to certain targeted therapies [17], it is possible that the C-5 subtype may be relatively resistant to inhibition of the PI3K-AKT-mTOR axis.…”
Section: Single-cell Inhibitor Screen Involving 300 Inhibition and Comentioning
confidence: 60%
“…Cell proliferation assay were performed as described previously 10 . Cells were incubated with DMSO or the serially diluted PF04691502 (0.1, 1.0, and 10 μmol/L).…”
Section: Methodsmentioning
confidence: 99%